1990
DOI: 10.1001/archderm.1990.01670300097016
|View full text |Cite
|
Sign up to set email alerts
|

Papular Acne Scars

Abstract: One hundred thirty-three patients were examined for the presence of a cutaneous eruption consisting of small, asymptomatic, hypopigmented, follicular papules on the upper part of the trunk. The papules were present in 57% of patients who had a history of acne vulgaris and in 9% of patients who denied ever having had acne. Biopsy specimens from five patients revealed circumscribed, perifollicular or parafollicular lesions in which both elastic and collagen fibers were attenuated in comparison with those in norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The most frequently described lesions are the depressed ones, indiscriminately referred as pitted or atrophic acne scars, 3–20 with few references to other morphologic patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently described lesions are the depressed ones, indiscriminately referred as pitted or atrophic acne scars, 3–20 with few references to other morphologic patterns.…”
Section: Discussionmentioning
confidence: 99%
“…These types of scars accumulate make‐up and sunscreen lotion, and the projection of their margins casts a dark shadow on the bottom. They can be subdivided into the following: (3.b.1) Superficial (dish‐like) are shallow defects (Figure 8) in which the only useful therapeutic approach is isolated use of ablative methods, including phenol chemical peeling, 1 dermabrasion, 2–13 chemabrasion, 14 and CO 2 3–15 or pulsed Erbium YAG 4–16 laser abrasion. (3.b.2) Medium (crater‐like) has a scar base that is relatively smooth and has normal color and texture and wide diameter (Figure 9) and can be treated by either of two ways: (1) the base is surrounded and cut by biopsy punches 17 or mini blades, followed by elevation with forceps until the clot formation, to keep it in the new position or (2) the shoulders can be sculpted and beveled to the peripheral skin by razabrasion 18 (using the razor blade as abrader), electrodesiccation 19 or CO 2 laser vaporization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, differential diagnosis of papular elastorrhexis should be established with other secondary anetodermas with small lesions, papular acne scars, 15 white fibrous papulosis of the neck, luetic secondarism, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al 12 reported that papular acne scars represent postacne scars and they are indistinguishable from those described as papular elastorrhexis. However, papular elastorrhexis differs from postacne scars in some aspects.…”
Section: Discussionmentioning
confidence: 99%